Prognostic significance of tissue factor in patients with pancreatic cancer: a systematic review protocol. Issue 9 (14th September 2020) - Li, Haiyuan; Yu, Yang; Shi, Qianling; Chen, Xueping; Zheng, Peng; Wang, Dengfeng; Tao, Pengxian; Gu, Baohong; Li, Xuemei; Zhang, Tao; Xiang, Lin; Xi, Dayong; et al.
Abstract : Introduction: Pancreatic cancer is a highly aggressive digestive system tumour with poor prognosis. Venous thromboembolism (VTE) is a well-known complication of pancreatic cancer, and tissue factor (TF) contributes to the generation of a hypercoagulable state and thrombotic disease in pancreatic cancer. Several studies showed that an elevated TF level was related to the development of VTE and influenced the survival of patients with pancreatic cancer. Thus, we wish to conduct a systematic review of literature to clarify the prognostic significance of TF in pancreatic cancer. Methods and analysis: Studies comparing the circulating microparticle-associated TF (MP TF) level between patients who had pancreatic cancer with and without VTE will be included to evaluate the roles of TF in VTE development. Studies comparing the survival data between patients with high TF expression and low TF expression will also be included to explore the association of TF expression with patient survival. The outcomes are plasma MP TF level and survival endpoints (overall and progression-free survival), respectively. Primary studies of any type published in English will be included. Two reviewers will search Medline, EMBASE and Cochrane databases from inception to June 2020, retrieve relevant studies, and independently select the literatures and extract data from the included studies. The quality of each included study will be assessed by the Newcastle-Ottawa Scale score. The HR and 95% CI of each study will be pooled for survival outcome, and the standardised mean difference (SMD) with 95% CIs will be used for continuous outcomes. If meta-analysis is inappropriate, the result will only be reported qualitatively. Subgroup and sensitivity analyses will be considered to identify sources of heterogeneity. The Grades of Recommendation, Assessment, Development and Evaluation method will be applied to assess the level of evidence of this systematic review. Ethics and dissemination: There are no concerning ethical issues. The results will be published. PROSPERO registration number: CRD42019133665.